2022
DOI: 10.3389/fnagi.2022.878278
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intermittent Hypoxia in Training Regimes and in Obstructive Sleep Apnea on Aging Biomarkers and Age-Related Diseases: A Systematic Review

Abstract: Several studies have assessed the effects of intermittent hypoxia-normoxia training (IHNT), intermittent hypoxia-hyperoxia training (IHHT), and obstructive sleep apnea (OSA) on aging and age-related diseases in humans; however, the results remain contradictory. Therefore, this review aims to systematically summarize the available studies on the effects of IHNT, IHHT, and OSA on aging and age-related diseases. Relevant studies were searched from PubMed, Google Scholar, Cochrane Library databases, and through ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 100 publications
0
7
0
3
Order By: Relevance
“…It should also be noted that there is strong evidence showing that the aging process and sleep debt are directly associated with increased inflammation [ 12 , 13 ]. An increase in inflammatory markers is typically observed in sleep disorders [ 14 , 15 ] and in conditions with reduced muscle function such as sarcopenia [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…It should also be noted that there is strong evidence showing that the aging process and sleep debt are directly associated with increased inflammation [ 12 , 13 ]. An increase in inflammatory markers is typically observed in sleep disorders [ 14 , 15 ] and in conditions with reduced muscle function such as sarcopenia [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…When ER stress intense, the UPR promotes cell death especially through activation of the pro-apoptotic transcription factor C/EBP homologous protein (CHOP), which was viewed as a major factors in triggering other damage related pathways [ 104 ]. Meanwhile, some genes related to apoptosis were upregulated in OSA patients since there was a positive correlation between the severity of sleep apnea and apoptotic cells [ 106 ]. Consistent evidences have also shown that chronic intermittent hypoxemia (CIH) have an effect on metabolic dysfunction such as lipid metabolism, insulin resistance and pancreatic beta cell dysfunction by regulatory enzymes of some metabolic and inflammatory parameters [ 98 , 106 ].…”
Section: Osa Correlated Signaling Pathwaymentioning
confidence: 99%
“…Meanwhile, some genes related to apoptosis were upregulated in OSA patients since there was a positive correlation between the severity of sleep apnea and apoptotic cells [ 106 ]. Consistent evidences have also shown that chronic intermittent hypoxemia (CIH) have an effect on metabolic dysfunction such as lipid metabolism, insulin resistance and pancreatic beta cell dysfunction by regulatory enzymes of some metabolic and inflammatory parameters [ 98 , 106 ]. Studies have shown that plasma Alzheimer’s biomarkers are higher in patients with OSA than in the control group, and the mechanism of action may be related to sleep disturbances and nighttime hypoxia [ 107 ].…”
Section: Osa Correlated Signaling Pathwaymentioning
confidence: 99%
“…Die zahlreichen Zielparameter dieser Studie wurden ohne jeden Querverweis getrennt in zwei Publikationen [16] [17] veröffentlicht, zusätzlich eine Mischung aus beiden auch auf Russisch [18]. Eine Priorisierung der Zielparameter ist nicht angegeben, insofern sind die zahlreichen Ergebnisse streng deskriptiv zu be-Langsame Atmung, wie sie in der Yoga-Pra- In der Gesamtbewertung dieser gegenteiligen Effekte könne vermutet werden, dass der Hauptfaktor, der die Richtung der intermittierenden Hypoxie bestimmt, ihre Intensität und Dauer ist [22].…”
Section: Kognition Bzw Dementielle Prozesseunclassified
“…Symptome des Alterungsprozesses (Aging) sich im Vergleich von 20 IHT-/IHHT-Studien mit 18 zum Schlafapnoe-Syndrom ergeben. Letztere kann auch als eine spontan auftretende Form von intermittierender Hypoxie betrachtet werden 22 . IIHHT habe positive Auswirkungen auf mehrere altersbezogene Parameter wie Lebensqualität, kognitive und körperliche Funktionen, Nüchtern-Blutzucker, Gesamtcholesterin, LDL, systolischen Blutdruck, rote Blutkörperchen und Entzündungsparameter.…”
Section: Hypoxie Als Therapieunclassified